Left Ventricular Hypertrabeculation Is Not Associated With Cardiovascular Morbity or Mortality: Insights From the Eurocmr Registry - Zemrak, Filip; Raisi-Estabragh, Zahra; Khanji, Mohammed Y.; Mohiddin, Saidi A.; Bruder, Oliver; Wagner, Anja; Lombardi, Massimo; Schwitter, Juerg; van Rossum, Albert C.; Pilz, Günter; Nothnagel, Detlev; Steen, Henning; et al. (Frontiers in Cardiovascular Medicine, 2020)
Aim: Left ventricular non-compaction (LVNC) is perceived as a rare high-risk cardiomyopathy characterised by excess left ventricular (LV) trabeculation. However, there is increasing evidence contesting the clinical significance of LV hyper-trabeculation and the existence of LVNC as a distinct cardiomyopathy. The aim of this study is to assess the association of LV trabeculation extent with cardiovascular morbidity and all-cause mortality in patients undergoing clinical cardiac magnetic resonance (CMR) scans across 57 European centres from the EuroCMR registry. Methods and Results: We studied 822 randomly selected cases from the EuroCMR registry. Image acquisition was according to international guidelines. We manually segmented images for LV chamber quantification and measurement of LV trabeculation (as per Petersen criteria). We report the association between LV trabeculation extent and important cardiovascular morbidities (stroke, atrial fibrillation, heart failure) and all-cause mortality prospectively recorded over 404 ±82 days of follow-up. Maximal non-compaction to compaction ratio (NC/C) was mean (standard deviation) 1.81 ±0.67, from these, 17% were above the threshold for hyper-trabeculation (NC/C >2.3). LV trabeculation extent was not associated with increased risk of the defined outcomes (morbidities, mortality, LV CMR indices) in the whole cohort, or in sub-analyses of individuals without ischaemic heart disease, or those with NC/C >2.3. Conclusion Among 882 patients undergoing clinical CMR, excess LV trabeculation was not associated with a range of important cardiovascular morbidities or all-cause mortality over approximately 12 months of prospective follow-up. These findings suggest that LV hyper-trabeculation alone is not an indicator for worse cardiovascular prognosis.